2017
DOI: 10.1002/eat.22746
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in disordered eating behaviors and body dissatisfaction among adolescents with type 1 diabetes: Results from diabetes MILES youth—Australia

Abstract: A large proportion of adolescents with type 1 diabetes, particularly females reported engaging in DEB. Similarly, high rates of body dissatisfaction were reported, though ideal body shape preferences differed by gender. Given the high levels of self-reported DEB and gender-based patterns of body dissatisfaction, future research needs to examine the effectiveness of routine screening of DEB and consider implementation of stepped care approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
66
5
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(93 citation statements)
references
References 58 publications
12
66
5
10
Order By: Relevance
“…Therefore, further studies are required to investigate the reasons for the higher number of male adolescents with type 1 diabetes and DEB. DEB were also a typical feature of girls in our study, with a prevalence that was higher than some previous studies (Doyle et al, ; Saßmann et al, ; Wisting et al, ) but lower than the study reported by Araia et al ().…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…Therefore, further studies are required to investigate the reasons for the higher number of male adolescents with type 1 diabetes and DEB. DEB were also a typical feature of girls in our study, with a prevalence that was higher than some previous studies (Doyle et al, ; Saßmann et al, ; Wisting et al, ) but lower than the study reported by Araia et al ().…”
Section: Discussioncontrasting
confidence: 72%
“…A common feature of patients with type 1 diabetes with DEB is skipping insulin shots as an attempt to lose weight (Araia et al, ; Baechle et al, ; De Paoli & Rogers, ; Saßmann et al, ). Since the definition of insulin restrictors was based both on reporting by the patients and on clinical evaluation, few of them classified as restrictors were found in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated body dissatisfaction has been reported in adolescent females with type 1 diabetes (Araia et al., ). Moreover, behaviors necessary for diabetes care such as carbohydrate monitoring, restriction and portion control, blood sugar control, and regular exercise have the potential to transition from healthful to pathological thereby increasing risk for EDs (Young‐Hyman & Davis, ).…”
Section: Discussionmentioning
confidence: 99%
“…Malnutrition in AN may lead to hypoglycemia and increase insulin resistance, whereas insulin administration may lead to increase in weight due to increased metabolic efficiency, likely worsening the ED (27). The contrasting weight fluctuations associated with T1DM (reduction in weight) and insulin treatment (increase in weight) represent a considerable burden for girls with AN (28), increasing their body dissatisfaction, weight preoccupation and drive to lose weight (29). Hence, adolescents with comorbid AN and T1DM show considerable difficulties in handling their illness (30), and their compliance and adherence with their treatment is limited (31).…”
Section: Case Descriptionsmentioning
confidence: 99%